MMP12 deficiency attenuates menthol e-cigarette plus house dust-mite effects on pulmonary iron homeostasis and oxidative stress - Rakeysha I. Pinkston; Matthew Schexnayder; Zakia Perveen; Ingeborg M. Langohr; Tomislav Jelesijevic; Arthur L. Penn; Alexandra Noël (Respiratory Research)
Abstract Background Little is known regarding the pulmonary effects induced by the inhalation of menthol-flavored e-cigarette aerosols on asthma exacerbation, despite the popularity of these devices and flavors among youth and young adults. In the lungs, matrix metalloproteinase 12 (MMP12) expressed and secreted by both alveolar macrophages and bronchial epithelial cells plays an essential role in airway remodeling, a key feature of severe asthma. In this study, we investigated the role of MMP12 in menthol-flavored e-cigarette aerosol exposures plus house-dust mite (HDM)-induced asthmatic responses. Methods We exposed wild-type (WT) and MMP12 knockout (KO) juvenile female mice to well-characterized menthol-flavored e-cigarette aerosols followed by either PBS or HDM treatment, and evaluated pulmonary outcomes in terms of iron metabolism, oxidative stress responses and pulmonary inflammation. Results We found high levels of iron in the menthol-flavored e-cigarette aerosol. This correlated with e-cigarette + HDM WT mice exhibiting disruption of pulmonary iron metabolism, suggesting a defense mechanism against iron-mediated toxicity. This was evidenced by altered lung protein concentrations of ferroportin, ferritin, lactoferrin, and transferrin, activation of the antioxidant response element (ARE) pathway and up-regulated expression of NQO1 in e-cigarette + HDM WT mice. Further, despite decreased neutrophilic inflammation, MUC5AC, an oxidative stress inducible mucin, was increased in the e-cigarette + HDM WT mice. In contrast, MMP12 KO mice were protected against iron-induced oxidative stress responses, highlighting a crucial role of MMP12 in this model. Conclusion These findings revealed in vivo evidence supporting a crucial role for iron metabolism in nicotine salt iron-rich ENDS aerosol toxicity.